IMPROVEMENT OF OPERATING PROPERTIES OF PARTS OF FLEXOGRAPHIC SHEET MACHINES - Киричек, Петр; Шостачук, Александр (SWorldJournal, 2020)
The urgency of the problem of developing the technological process of formation of regular microrelief (RM) on the guides of flexographic sheet-fed machines is caused by insufficient accuracy of positioning of corrugated cardboard blanks when fed to the p